Identifying the Basement Structure of the Sula Fault Zone in the Banggai-Sula Microcontinent Region, Molucca Sea, based on 2D Gravity Inversion Modelling using Particle Swarm Optimisation and 3D Modelling using Grablox (Rudarsko-geološko-naftni zbornik, 2025)
This study aims to delineate the basement structure of Sula fault zones within the Banggai-Sula Microcontinent Region through the implementation of 2D and 3D gravity inversion modelling. The Sula fault is a consequence of the convergence between the Banggai-Sula Microcontinent and northern regions, or the compression caused by the extrusion of material from the Molucca Sea collision zone to the south. This is an active fault, with a few earthquakes in the last two decades. As a complex active fault, this presents several questions, particularly about the fault's structure. Residual anomaly data was modelled in two dimensions using Particle Swarm Optimisation method and in three dimensions with Grablox software. The gravity inversion results indicate that the basement depth in the nine profile incision zones, which are perpendicular to the fault zone, range from 120 m to 9308 m. This research region can be separated into two fault zones based on the low-value residual anomalies. Fault zone 1 exhibits a basement depth range of 2843.3 m to 6526.9 m. This region has rock components with a low density ranging from 1.68 g/cm³ to 2.20 g/cm³. Fault zone 2 exhibits a basement depth range of 3716.3 m to 9308.4 m. The geological layer comprises constituent rocks with a low density of 1.24 g/cm³, in contrast to the northern rocks averaging 2.4 g/cm³ and the southern rocks averaging between 2.5 g/cm³ and 2.7 g/cm³.The average depth of faults in fault zones 1 and 2 is 5200 m. The inversion method using PSO can yield estimates for the basement depth of the fault zone. Derivative analysis indicates that the east-west-trending fault structure in fault zone 1 and fault zone 2 aligns with the tectonic characteristics of the Banggai-Sula microcontinent, hence affirming the presence of an east-west fault in the area.